Mathe – nein danke? Interesse im und am Mathematikstudium bei Grundschullehramtsstudierenden mit Pflichtfach - Kolter, Jana; Liebendörfer, Michael (Mathematik im Übergang Schule / Hochschule und im ersten Studienjahr)

Interest and Self-Determination in the Transition to Studying Mathematics - Liebendörfer, Michael; Hochmuth, Reinhard (Proceedings of the 37th Conference of the International Group for the Psychology of Mathematics Education)

Interest in Mathematics and the First Steps at the University - Liebendörfer, Michael; Hochmuth, Reinhard (Proceedings of the 8th Conference of European Research in Mathematics Education)

Surface Diffusion of 3d-Metals on W(110) - Reuter, Dirk; Gerth, Gerhard; Kirschner, J. (Surface Diffusion)

Werte als Ausgangsbasis der Berufsorientierung in Justizvollzugsanstalten - Beutner, Marc; Rohde, S (Berufsorientierung, Gewaltsensibilisierung und Kompetenzentwicklung. Konzepte zur beruflichen Bildung im Jungtätervollzug)

Ausbildungsfähigkeit und Basiskompetenzen – Eine Herausforderung für den Justizvollzug - Beutner, Marc; Rose, S (Berufsorientierung, Gewaltsensibilisierung und Kompetenzentwicklung. Konzepte zur beruflichen Bildung im Jungtätervollzug)

Middeke,M. / Schnierer, P.P. / Sierz, A. (Hg.): The Methuen Guide to Contemporary British Playwrights - Tönnies, Merle (Anglia)

Rossow, H. Globalismus und Lew Labour - Tönnies, Merle (Anglistik. International Journal of English Studies)

Baumbach, S. / Neumann, B. / Nünning, A.: A History of British Drama - Tönnies, Merle (Anglistik. International Journal of English Studies)

COR-VET – Career Orientation in Vocational Education and Training in Europe - Beutner, Marc; Fortmann, L. M. (Kölner Zeitschrift für Wirtschaft und Pädagogik)

Classroom Response Systeme - Beutner, Marc; Kundisch, Dennis; Magenheim, J; Hermann, P; Reinhardt, W; Zoyke, A (Informatik Spektrum)

"This Bright Inward Cinema of Thought" – Stream of Consciousness in Contemporary English Fiction - Strauß, Sara

‘Monstrous’ Homes: How Private Spaces Shape Characters’ Identities in 19th-century Sensation Fiction - Flotmann, Christina (Monstrous Geographies: Places and Spaces of the Monstrous)

Ambiguity in ‘Star Wars’ and ‘Harry Potter’: A (Post-)Structuralist Reading of Two Popular Myths - Flotmann, Christina

Populäre Mythen bei Star Wars und Harry Potter - Flotmann, Christina
Interview 2 Feb. 2013

Increasing the power of piezoelectric energy harvesters by magnetic stiffening - Al-Ashtari, Waleed; Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Journal of Intelligent Material Systems and Structures)
A piezoelectric cantilever beam with a tip mass at its free end is a common energy harvester configuration. This article introduces a new principle of designing such a harvester that increases the generated power without changing the resonance frequency of the harvester: the attraction force between two permanent magnets is used to add stiffness to the system. This magnetic stiffening counters the effect of the tip mass on the efficient operation frequency. Five set-ups incorporating piezoelectric bimorph cantilevers of the same type in different mechanical configurations are compared theoretically and experimentally to investigate the feasibility of this principle: theoretical and experimental results show that magnetically stiffened harvesters have important advantages over conventional set-ups with and without tip mass. They generate more power while only slightly increasing the deflection in the piezoelectric harvester and they can be tuned across a wide range of excitation frequencies.

Enhanced energy harvesting using multiple piezoelectric elements: Theory and experiments - Al-Ashtari, Waleed; Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Sensors and Actuators A: Physical)
Power and bandwidth of piezoelectric harvesters can be increased by using multiple piezoelectric elements in one harvester. In this contribution, a novel energy harvesting cantilever array with magnetic tuning including three piezoelectric bimorphs is investigated theoretically and experimentally, with a good agreement between model and experiment. Other than harvester designs proposed before, this array is easy to manufacture and insensitive to manufacturing tolerances because its optimum operation frequency can be re-adjusted after fabrication. Using the superposition principle, the Butterworth-Van Dyke model and a mechanical lumped parameters model, the generated voltage and current are determined analytically. Formulas for calculating the power generated by array harvesters with an arbitrary number of piezoelectric elements connected in series or in parallel are derived. It is shown that optimum harvester design must take both the connected load and the operating frequency into account. Strategies for connecting multiple bimorphs to increase the maximum generated power and/or enhance the bandwidth compared to a single bimorph harvester are investigated. For bandwidth enhancement it is essential that individual rectifiers are used for the bimorphs. An example with three bimorphs shows that, depending on the chosen tuning strategy, the power is increased by about 340% or the bandwidth is increased by about 500%, compared to one single bimorph.
Keywords: Energy harvesting; Cantilever array; Bandwidth; Power increase

Characteristics of Piezoelectric Energy Harvesters in Autonomous Systems - Al-Ashtari, Waleed; Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Proceedings of 10th International Workshop on Piezoelectric Materials and Applications and 8th Energy Harvesting Workshop, Hannover, Germany, 14.-17.7.2013)
A basic autonomous system powered by a piezoelectric harvester contains three components apart from the harvester: a fullwave rectifier, a reservoir capacitor and an electronic device performing the primary task of the system. In this contribution, a model describing the operation of such a system is derived. It is found that in steady-state operation, the piezoelectric harvester experiences two alternating load conditions due to the rectification process. These alternating load conditions can have a significant effect on the operation of the harvester and must be considered in the design of autonomous systems. The results also show that such an autonomous system works efficiently if it is connected to a high impedance load and excited by a frequency matching the anti-resonance frequency of the piezoelectric harvester.
Keywords: Energy harvesting; harvester modeling; load dependence; generated voltage

A friction based approach for modeling wire bonding - Althoff, Simon; Neuhaus, Jan; Hemsel, Tobias; Sextro, Walter (IMAPS 2013, 46th International Symposium on Microelectronics)
A model approach for wedge/wedge bonding copper wire is presented. The connection between wire and substrate is based on a variety of physical effects, but the dominant one is the friction based welding while applying ultrasound. Consequently, a friction model was used to investigate the welding process. This model is built up universal and can be used to describe the formation of micro welds in the time variant contact area between wire and substrate. Aim of the model is to identify the interactions between touchdown, bond normal force, ultrasonic power and bonding time. To do so, the contact area is discretized into partial areas where a Point Contact Model is applied. Based on this approach it is possible to simulate micro and macro slip inside the contact area between wire and substrate. The work done by friction force is a main criterion to define occurring micro joints which influence the subsequent welding.
Keywords: Wire bonding; friction modeling; wire bond quality; contact element modeling

Influences of Bonding Parameters on the Tool Wear for Copper Wire Bonding - Eichwald, Paul; Sextro, Walter; Althoff, Simon; Eacock, Florian; Schnietz, Mark; Guth, Karsten; Brökelmann, Michael (15th Electronics Packaging Technology Conference)
Ultrasonic wire bonding is a common technology for manufacturing electrical interconnects. In the field of power electronics, new thermal and electrical obligations arose due to increasing power density requirements. One approach to achieve these aims is replacing the wire material for heavy wire bonds from aluminum to copper. This material change leads to challenging tasks and problems, for instance the occurring wear of the bond tool. The wear is significantly higher using copper wire instead of aluminum and results in a dramatic loss in the amount of interconnects which can be produced reliable by a single tool. To reduce setting-up time in the production and minimizing costs, an enlarged bonding tool lifetime is desirable. Therefore, the paper discusses the influences of bonding parameters on the wear. The key question is which of the tasks cannot be fulfilled with increased wear of the tool, e.g. loss of process capability. The main functions are fixing the wire in the tool groove, predeformation, applying normal force and transmission of ultrasonic oscillation to the wire. To identify the most affecting factors, four bonding parameters are varied and their influences are investigated. These parameters are: (I) ultrasonic power, (II) tool geometry, (III) the way of tangential force transmission and (IV) loop trajectory.

Leistungs- und Bandbreitensteigerung von Energy-Harvesting-Generatoren für Energieautarke Systeme - Hunstig, Matthias; Al-Ashtari, Waleed; Hemsel, Tobias; Sextro, Walter (9. Paderborner Workshop Entwurf mechatronischer Systeme)

High-Velocity Slip-Slip Operation of Piezoelectric Inertia Motors - Experimental Validation - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Proceedings of 10th International Workshop on Piezoelectric Materials and Applications and 8th Energy Harvesting Workshop)
It has been shown previously that ``slip-slip'' operation of piezoelectric inertia motors allows higher velocities and smoother movements than classic ``stick-slip'' operation. One very promising driving option is to use a superposition of multiple sinusoidal signals. In this contribution, previous theoretical results are validated experimentally. The results confirm the theoretical result that for a given maximum frequency, usually defined by the actuator characteristics, a signal with high fundamental frequency and consisting of two superposed sine waves leads to the highest velocity and the smoothest motion. This result is of fundamental importance for the further development of high-velocity piezoelectric inertia motors.
Keywords: Piezoelectric inertia motor; stick-slip motor; driving signal; velocity; smoothness

Modelling the friction contact in an inertia motor - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Journal of Intelligent Material Systems and Structures)
Piezoelectric inertia motors, also known as stickslip drives or (smooth) impact drives, use the inertia of a body to drive it by a friction contact in small steps, in the majority of motors composed of a stick phase and a slip phase between the friction partners. For optimizing inertia motors, it is important to understand the friction contact correctly and to measure its properties appropriately. This contribution presents experimental set-ups for measuring the contact force, friction force and relative displacement in an actual inertia motor with a dry friction contact and numerical simulations of the motor operation. The motor uses a pre-stressed multilayer actuator with a displacement in the range of 20 $μ$ m. It is shown that a previously postulated condition for the applicability of simple kinetic friction models is well fulfilled for the investigated motor. The friction contact in the motor is simulated using different kinetic friction models. The input for the friction models is the measured motion of the rod. The models qualitatively reproduce the measured motion but show quantitative deviations varying with frequency. These can be explained by vibrations of the driving rod that are experimentally investigated.
Keywords: Actuator; friction; motor; piezoelectric

Stick-slip and slip-slip operation of piezoelectric inertia drives - Part II: Frequency-limited excitation - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Sensors and Actuators A: Physical)
This contribution provides a systematic investigation and performance comparison of different modes of operation for piezoelectric inertia drives. The movement of these motors is classically assumed to consist of steps involving stiction and sliding, resulting in the term ``stick-slip drives''. In the first part of this contribution it has been found that using ideal driving signals, ``slip-slip'' operation without phases of stiction allows very high velocities, while the maximum velocity is limited principally in stick-slip operation. In this part it is shown that slip-slip operation is also suitable for use with real actuators, driven with frequency-limited versions of the ideal signals presented in part I. The motional performance of the motor as well as its wear and the required electric power are investigated for operation with different signals. It is found that for high velocity inertia motors it is recommendable to use actuators with large stroke and to drive them with a signal consisting of two harmonics at a high fundamental frequency, a result that is supported by similar setups implemented experimentally by other authors. Using Lanczos' σ factors to calculate the frequency-limited excitation signals instead of standard Fourier series additionally increases the motor performance significantly. The results help motor designers to choose the appropriate mode of operation and to optimise the motor parameters for their individual applications.
Keywords: Inertia motor

Stick-slip and slip-slip operation of piezoelectric inertia drives - Part I: Ideal Excitation. - Hunstig, Matthias; Hemsel, Tobias; Sextro, Walter (Sensors and Actuators A: Physical)
Piezoelectric inertia motors, also known as ``stick--slip drives'', use the inertia of a body to drive it in small steps by means of a friction contact. While these steps are classically assumed to involve stiction and sliding, the motors can also operate in ``slip--slip'' mode without any phase of static friction. This contribution provides a systematic investigation and performance comparison of different stick--slip and slip--slip modes of operation. Different criteria for comparing the motional performance of inertia motors are defined: Steady state velocity, smoothness of motion, and start-up time. Using the example of a translational inertia motor excited by an ideal displacement signal, it is found that the maximum velocity reachable in stick--slip operation is limited principally, while continuous slip--slip operation allows very high velocities. For the investigated driving signals, the motor velocity is proportional to the square root of the actuator stroke. The motor performance with these ideal signals defines an upper boundary for the performance of real motors.
Keywords: Inertia motor; Stick--slip drive; Mode of operation; Performance indicator; Velocity maximization; Actuator stroke

Machinery Prognostic Method Based on Multi-Class Support Vector Machines and Hybrid Differential Evolution -- Particle Swarm Optimization - Kimotho, James Kuria; Sondermann-Wölke, Christopher; Meyer, Tobias; Sextro, Walter (Chemical Engineering Transactions)
Recently, focus on maintenance strategies has been shifted towards prognostic health management (PHM) and a number of state of the art algorithms based on data-driven prognostics have been developed to predict the health states of degrading components based on sensory data. Amongst these algorithms, Multiclass Support Vector Machines (MC-SVM) has gained popularity due to its relatively high classification accuracy, ability to classify multiple patterns and capability to handle noisy /incomplete data. However, its application is limited by the difficulty in determining the required kernel function and penalty parameters. To address this problem, this paper proposes a hybrid differential evolution -- particle swarm optimization (DE-PSO) algorithm to optimize the MC-SVM kernel function and penalty parameters. The differential algorithm (DE) obtains the search limit for the SVM parameters, while the particle swarm optimization algorithm (PSO) determines the global optimum parameters for a given training data set. Since degrading machinery components display several degradation stages in their lifetime, the MC-SVM trained with optimum parameters are used to estimate the health states of a degrading machinery component, from which the remaining useful life (RUL) is predicted. This method improves the classification accuracy of MC-SVM in predicting the health states of a machinery component and consequently increases the accuracy of RUL predictions. The feasibility of the method is validated using bearing prognostic run-to-failure data obtained from NASA public data repository. A comparative study between MC-SVM with parameters obtained using simple grid search with n-fold cross validation and MCSVM with DE-PSO based on prognostic performance metrics reveals that the proposed method has better performance, with all the cases considered falling within a 10 % error margin. The method also outperforms other soft computing methods proposed in literature.

Application of Event Based Decision Tree and Ensemble of Data Driven Methods for Maintenance Action Recommendation - Kimotho, James Kuria; Sondermann-Wölke, Chritoph; Meyer, Tobias; Sextro, Walter (International Journal of Prognostics and Health Management)
This study presents the methods employed by a team from the department of Mechatronics and Dynamics at the University of Paderborn, Germany for the 2013 PHM data challenge. The focus of the challenge was on maintenance action recommendation for an industrial machinery based on remote monitoring and diagnosis. Since an ensemble of data driven methods has been considered as the state of the art approach in diagnosis and prognosis, the first approach was to evaluate the performance of an ensemble of data driven methods using the parametric data as input and problems (recommended maintenance action) as the output. Due to close correlation of parametric data of different problems, this approach produced high misclassification rate. Event-based decision trees were then constructed to identify problems associated with particular events. To distinguish between problems associated with events that appeared in multiple problems, support vector machine (SVM) with parameters optimally tuned using particle swarm optimization (PSO) was employed. Parametric data was used as the input to the SVM algorithm and majority voting was employed to determine the final decision for cases with multiple events. A total of 165 SVM models were constructed. This approach improved the overall score from 21 to 48. The method was further enhanced by employing an ensemble of three data driven methods, that is, SVM, random forests (RF) and bagged trees (BT), to build the event based models. With this approach, a score of 51 was obtained . The results demonstrate that the proposed event based method can be effective in maintenance action recommendation based on events codes and parametric data acquired remotely from an industrial equipment.
Keywords: maintenance decision; Bagged trees; Decision trees; PSO-SVM; Random forests

Grundlagen medienbezogener Schulentwicklung - Herzig, Bardo; Klar, Tilman-Mathies (Lernende Schule - Medienkompetenz entwickeln)

Modelbased Investigations of Gyroscopic Effect on the (Elasto-)Kinematics of Suspension Systems - Kohl, Sergej; Zuber, Armin; Sextro, Walter (Proc. Appl. Math. Mech.)
During wheel bumping caused by stochastic road excitation, the wheel performs rotational and translational movements. The bump and rebound wheel velocity leads to significant angular velocities based on the (elasto-)kinematics of the suspension system. Based on the gyroscopic effect, moments arise about the rotating wheel induced by the angular change while bumping. Therefore it leads to undesirable wheel changes and degrades the tire contact and finally decreases the driving stability. A flexible MBS-model of the five-link rear axle system that includes these effects has been built up to allow a detailed investigation of the gyroscopic effect. Using the simulation results, conclusions can be drawn for refining design criteria for the kinematics, elastokinematics and topology of the suspension system to increase the active safety of the vehicle

2PC-Recu-Module for energy recovery at hydraulic driven injection molding machines - Lenzen, Marco; Unger, Andreas; Wortberg, Johannes

Multiobjective Optimization including Safety of Operation Applied to a Linear Drive System - Meyer, Tobias; Hölscher, Christina; Menke, Michael; Sextro, Walter; Zimmer, Detmar (Proc. Appl. Math. Mech.)
In this contribution, we introduce a multiobjective optimization used to calculate safe optimal working points for a mechatronic system by including stochastic safety-critical signals in an objective function. Our application example consists of a linear drive for a rail-bound vehicle and an actuation unit. The linear drive's secondary part is fixed; the primary part is vehicle-mounted and can be adjusted vertically to account for deviations of the height of the secondary part. A small air gap between both parts improves efficiency, but increases the risk of a collision between the two parts. Using height data of the secondary part, a trajectory for the vertical adjustment of the primary part is calculated. However, unexpected deviations necessitate a readjustment of the air gap. The probability of such unexpected height deviations can be calculated from the readjustment data. The system is equipped with sensors to measure the air gap. Assuming that the sensor noise is normally distributed, noise characteristics are determined. Using this information and the probability distribution of unexpected height deviations, the probability of a collision is determined.T he sensor noise and the probability of a collision between both parts of the linear drive are included in the dynamical model of the system. Using multiobjective optimization, pareto-optimal working points for the controller of the air gap are obtained. By selecting an appropriate working point, safe operation can be ensured.

Increasing Intelligent Systems' Reliability by Using Reconfiguration - Meyer , Tobias; Henning Keßler, Jan; Sextro, Walter; Trächtler, Ansgar (Proceedings of the Annual Reliability and Maintainability Symposium (RAMS))
Self-optimizing mechatronic systems allow the adaptation of the system's behavior to the current situation. This can be used to actively adapt the behavior to the current degradation state of the system or of some of its components. To this end, the Multi-Level Dependability Concept has been developed. In this contribution, we show how the Multi-Level Dependability Concept has been applied to the active suspension module of an innovative rail-bound vehicle. For this module, the usage of control reconfiguration, which is a novel approach to exploit complex redundancy systems, is required. We show that by combining self-optimization with the possibilities given by control reconfiguration, the dependability of a complex mechatronic system can be greatly improved.

Controlling the Remaining Useful Lifetime using Self-Optimization - Meyer, Tobias; Sondermann-Wölke, Christoph; Kimotho, James Kuria; Sextro, Walter (Chemical Engineering Transactions)
Self-optimizing mechatronic systems offer possibilities well beyond those of traditional mechatronic systems. Among these is the adaptation of the system behavior to the current situation. To do so, they are able to choose from different working points, which are pre-calculated using multiobjective optimization and are thus Pareto-optimal with regard to the chosen objective functions. In this contribution, a method is presented that allows to continuously control the system degradation by adapting the behavior of a selfoptimizing system throughout its complete lifetime. The current remaining useful lifetime is estimated and then related to the spent lifetime and the desired useful lifetime. Using this information, a reliability-related objective is prioritized using a closed-loop control, which in turn is used to determine the working point of the self-optimizing system. This way, the desired useful lifetime can be achieved. To exemplify the setup of the controller structure and to demonstrate the adaptation of the system behavior, a dynamic model of a clutch system is used. It can be seen that the closed loop controller is able to correct for external perturbations, such as changed requirements, as well as changed system parameters. This way, the modeled system is able to achieve the desired lifetime reliably.

Bewertung der Zuverlässigkeit selbstoptimierender Systeme mit dem LARES-Framework - Meyer, Tobias; Sondermann-Wölke, Christoph; Sextro, Walter; Riedl, Martin; Gouberman, Alexander; Siegle, Markus (9. Paderborner Workshop Entwurf mechatronischer Systeme)
Selbstoptimierende mechatronische Systeme bieten die Möglichkeit, ihr Verhalten an geänderte Umgebungsbedingungen anzupassen. Dazu werden beispielsweise redundante Strukturen genutzt, Reglerparameter angepasst oder Regelstrategien umgeschaltet. Dies kann auch genutzt werden, um die Zuverlässigkeit des Systems zu steigern. Zugleich entstehen aber durch die gesteigerte Komplexität dieser Systeme zusätzliche Risiken. Um sicherzustellen, dass das System dennoch die gestellten Anforderungen bezüglich der Zuverlässigkeit erfüllt, ist eine Modellierung des Gesamtsystems und anschließende Zuverlässigkeitsbewertung notwendig. Dies ist aufgrund der situationsabhängigen Verhaltensanpassung und des nicht intuitiv vorhersehbaren Verhaltens jedoch nicht mit klassischen Verfahren möglich. Ein Modellierungsverfahren, das diese Eigenschaften abbilden kann, ist LARES (LAnguage for REconfigurable dependable Systems). Die Anwendung von LARES zur Bewertung der Zuverlässigkeit eines selbstoptimierenden Systems wird anhand des Feder-Neige-Moduls gezeigt. Es ist eine Baugruppe der Fahrzeuge eines innovativen Bahnsystems, der RailCabs. Das Feder-Neige-Modul dient dazu, unerwünschte Schwingungen des Fahrzeugaufbaus zu minimieren. Mit LARES können die Hardware-Komponenten des Systems, ihre in Abhängigkeit von der aktuellen Situation veränderten Belastungen sowie die nicht-deterministische Verhaltensadaption modelliert werden.

Selected Papers from the 9th International Workshop on Piezoelectric Materials and Applications in Actuators (Sensors and Actuators A: Physical)
The 9th International Workshop on Piezoelectric Materials and Applications in Actuators (IWPMA 2012) was successfully held on 22–25 April 2012 in Hirosaki, Japan. The general chair was Prof. M.K. Kurosawa from the Tokyo Institute of Technology, Japan. In the past, Korea, Germany, Turkey, China, and USA have hosted the annual conference, but this was the first time for the annual IWPMA conference to be held in Japan. The IWPMA 2012 was organized as a joint symposium with JTTAS Smart Actuator/Sensor Study Committee and ICAT International Actuator Symposium. More than 150 people from the world (12 countries) participated and had fruitful discussions with 138 presentations including 11 invited talks. In addition to piezoelectric materials and piezoelectric actuators, the presentation topics were expanded to include solid-state actuators, energy harvesting, multifunctional materials, and other current important issues. It is our honor to pronounce that the “Sensors and Actuators A” journal has published this special issue on the IWPMA 2012 including the best 25 contributions. This issue covers the functional materials, such as piezoelectric and magnetostrictive materials, and their applications. However, for the innovative devices, various ideas concerning materials, mechanisms, designs, fabrication process, and control-systems are also required to be organically combined. From the view of this concept, we believe the published 25 papers can excite the researcher's intellectual curiosity concerning these issues and can serve as the driving force for further breakthroughs. Please enjoy the latest research results selected by our editor team. Finally, we appreciate all participants in the IWPMA 2012 and the devoted reviewers for the publication. We hope that the papers in this special issue will open up the next researches, which will be presented in the future IWPMA conferences.

Study on optimizing ultrasonic irradiation period for thick polycrystalline PZT film by hydrothermal method - Ohta, Kanako; Isobe, Gaku; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (Ultrasonics)
The hydrothermal method utilizes a solution-based chemical reaction to synthesize piezoelectric thin films and powders. This method has a number of advantages, such as low-temperature synthesis, and high purity and high quality of the product. In order to promote hydrothermal reactions, we developed an ultrasonic assisted hydrothermal method and confirmed that it produces dense and thick lead--zirconate--titanate (PZT) films. In the hydrothermal method, a crystal growth process follows the nucleation process. In this study, we verified that ultrasonic irradiation is effective for the nucleation process, and there is an optimum irradiation period to obtain thicker PZT films. With this optimization, a 9.2-$μ$ m-thick PZT polycrystalline film was obtained in a single deposition process. For this film, ultrasonic irradiation was carried out from the beginning of the reaction for 18 h, followed by a 6 h deposition without ultrasonic irradiation. These results indicate that the ultrasonic irradiation mainly promotes the nucleation process.
Keywords: Piezoelectric material

Piezoelectric Properties of CuO-Doped (K,Na)NbO3 Lead-Free Ceramics Synthesized with Hydrothermal Powders - Yokouchi, Yuriko; Maeda, Takafumi; Bornmann, Peter; Hemsel, Tobias; Morita, Takeshi (Japanese Journal of Applied Physics)
We report the piezoelectric properties of CuO-doped hydrothermal (K,Na)NbO3 ceramics that can be applied as hard-type lead-free piezoelectric ceramics. To date, we have succeeded in synthesizing high-quality KNbO3 and NaNbO3 powders by the hydrothermal method, which is based on an ionic reaction at high temperature (around 210 $\,^{°}$C) and pressure. Increasing both the piezoelectric constant d and the mechanical quality factor (Qm) is important for resonance-type piezoelectric devices, such as ultrasonic motors and transformers. CuO doping into hydrothermal (K,Na)NbO3 ceramics was examined to realize hard-type lead-free piezoelectric ceramics. By doping with 1.2 mol % CuO, Qm was increased and the dielectric loss (tan δ) was decreased to 0.5%. The grain size was also influenced by the amount of CuO doping, which indicates that Qm is related to the density. To achieve a higher Qm value, the grain size is required to be less than 5 µm; however, excessive CuO doping leads to anomalous grain growth. Optimal piezoelectric properties were obtained for 1.2 mol % CuO-doped (K,Na)NbO3; k31 = 0.32, d31 = -44 pC/N, Qm (radial) = 959, and tan δ= 0.5%. These characteristics showed that CuO doping with hydrothermal powders is effective for obtaining hard-type ceramics, and the mechanical quality factor is more than ten times higher than that of nondoped hydrothermal (K,Na)NbO3 ceramics. Therefore, compared with the conventional solid-state method, we could succeed in obtaining hard-type ceramics by a simple and short process.

Cubic GaN quantum dots embedded in zinc-blende AlN microdisks - Bürger, M.; Kemper, R.M.; Bader, C.A.; Ruth, M.; Declair, S.; Meier, Cedrik; Förstner, Jens; As, D.J. (Journal of Crystal Growth)
Microresonators containing quantum dots find application in devices like single photon emitters for quantum information technology as well as low threshold laser devices. We demonstrate the fabrication of 60 nm thin zinc-blende AlN microdisks including cubic GaN quantum dots using dry chemical etching techniques. Scanning electron microscopy analysis reveals the morphology with smooth surfaces of the microdisks. Micro-photoluminescence measurements exhibit optically active quantum dots. Furthermore this is the first report of resonator modes in the emission spectrum of a cubic AlN microdisk.
Keywords: tet_topic_qd; tet_topic_microdisk

Whispering gallery modes in zinc-blende AlN microdisks containing non-polar GaN quantum dots - Bürger, M.; Ruth, M.; Declair, S.; Förstner, Jens; Meier, Cedrik; As, Donat Josef (Applied Physics Letters)
Whispering gallery modes (WGMs) were observed in 60 nm thin cubic AlN microdisk resonators containing a single layer of non-polar cubic GaN quantum dots. Freestanding microdisks were patterned by means of electron beam lithography and a two step reactive ion etching process. Micro-photoluminescence spectroscopy investigations were performed for optical characterization. We analyzed the mode spacing for disk diameters ranging from 2-4 lm. Numerical investigations using three dimensional finite difference time domain calculations were in good agreement with the experimental data. Whispering gallery modes of the radial orders 1 and 2 were identified by means of simulated mode field distributions.
Keywords: tet_topic_qd; tet_topic_microdisk

„Sekretärin des Vorstandes “gesucht: Stellenanzeigen und die expressive Funktion des AGG - Bauhoff, Frauke; Schneider, Martin (Industrielle Beziehungen/The German Journal of Industrial Relations)

„Sekretärin des Vorstandes“ gesucht: Stellenanzeigen und die expressive Funktion des AGG - Bauhoff, Frauke; Schneider, Martin (Industrielle Beziehungen/The German Journal of Industrial Relations)

Cubic GaN on nano-patterned 3C-SiC/Si (001) substrates - Kemper, R.M.; As, Donald; Lindner, Jörg (Silicon-based Nanomaterials)

Colloidal nano-lithography: state-of-the-art - Brassat, Katharina; Pauly, Johannes; Kemper, R.; Strake, M.; Brodehl, Christoph; Sievers, Werner; Riedl, Thomas; Lindner, Jörg

Self-organization of nanospheres in trenches on silicon surfaces - Brassat, Katharina; Assion, Fabian; Hilleringmann, Ulrich; Lindner, Jörg (physica status solidi (a))
The selective deposition and self-assembly of nanospheres from a colloidal suspension in trenches on silicon surfaces is investigated using conventional light, confocal laser scanning and scanning electron microscopy. Trenches with widths of one to several nanosphere diameters are formed on silicon surfaces by photolithography and reactive ion etching. The spreading knife convective self-assembly technique is employed to distribute the nanosphere suspension on the pre-patterned surface. It is shown that this technique is particularly useful in combination with a functionalized surface where a selfassembled molecular monolayer changes the contact angle such that sphere deposition takes place almost exclusively in the trenches. By this, lines selectively filled with a chain of beads with a length of 0.5 mm have been achieved.

Selective deposition of nanospheres in trenches on silicon surfaces by self-organisation - Brassat, Katharina; Lindner, Jörg

Tailored structures produced via nanosphere lithography - Brodehl, Christoph; Greulich-Weber, Siegmund; Lindner, Jörg

Dewetting and Redistribution of an Au Catalyst on Nanopatterned 3C-SiC/Si (001) Surfaces - Dogan, M.; Kemper, R.M.; Lindner, Jörg

Characterization of cubic GaN/AlN multi-quantum wells using state-of-the-art analytical STEM - Lindner, Jörg; Kemper, R.M.; As, Donald; Meeertens, D.; Kovács, A.; Luysberg, M.; Tillmann, K.

Nanosphere lithography for device fabrication - Lindner, Jörg (SPIE Newsroom)

Nickel Nanodot Arrays on Silicon formed by Nanosphere Lithography: A TEM Study - Pauly, Johannes; Lindner, Jörg